Investigations of the machining of glasses and other normally brittle materials in the ductile regime - Chao, C. L. (Cranfield University, 1991)
Increased demands for precision components made of brittle materials such as glasses and advanced ceramics, are such that conventional (free abrasive) grinding and polishing techniques can no longer meet the requirements of today’s precision manufacturing engineering. Both fast production rates and high quality surfaces of complex shapes are required in addition to the spherical or planar surfaces produced which are most readily produced by conventional free abrasive techniques. The work investigates the feasibility of using ductile-mode single-point diamond turning both as an alternative machining technique in its own right and as a model for certain parameters involved in (rigid-wheel) grinding. Indentation and ruling/scribing were used to study the underlying material properties, mechanical stress fields, the ductile-brittle transition and material removal mechanisms. Several material removal mechanisms were identified and discussed; these were ploughing, cutting, delamination and brittle fracture. The results of indentation and scribing experiments show that, with penetration depth of less than a critical value (the critical cut depth) brittle materials can be machined in a ductile manner and with chips very similar to those obtained from the classical ductile cutting of metal, save that, in this case it is at a much smaller scale. The influence of tool shape has shown to be important in determining the material removal mechanism. The experiments on single-point diamond turning (facing) machine were carried out on a highly stiff diamond facing machine. During the present project continuous machining of a number of materials to Ra values of nanometres order has been achieved, these include soda-lime glass, fused silica, Zerodur and single crystal silicon. Ductile crack-free machining has been demostrated at spindle speeds up to 4500 rpm. The technical feasibility of ultra-fine single-point machining of optical, electronic and ceramic materials has thus been established. Investigations were undertaken into methods of measuring the nature and extent of sub-surface damage (SSD) using scanning acoustic microscope (SAM), Rutherford back-scattering technique (RBS) and X-ray topography. The results of SSD studies suggested that coarse machining marks could still be detected in the sub-surface region even though the surface has been subsequently machined to a condition of no (optically) visible damage.